The type of carbohydrates specifically selects microbial community structures and fermentation patterns. (December 2016) - Chatellard, Lucile; Trably, Eric; Carrère, Hélène
Graphical abstract: Highlights: Higher amounts of hydrogen were recovered from pentose than hexose fermentation. Lactate pathway was preferentially used from hexoses. Carbohydrate types structured bacterial communities and metabolic patterns. Degree of polymerisation is detrimental to hydrogen production. Ruminococcaceae bacteria likely played an important role in hydrolytic activity. Abstract: The impact on dark fermentation of seven carbohydrates as model substrates of lignocellulosic fractions (glucose, cellobiose, microcrystalline cellulose, arabinose, xylose, xylan and wheat straw) was investigated. Metabolic patterns and bacterial communities were characterized at the end of batch tests inoculated with manure digestate. It was found that hydrogen production was linked to the sugar type (pentose or hexose) and the degree of polymerisation. Hexoses produced less hydrogen, with a specific selection of lactate-producing bacterial community structures. Maximal hydrogen production was five times higher on pentose-based substrates, with specific bacterial community structures producing acetate and butyrate as main metabolites. Low hydrogen amounts accumulated from complex sugars (cellulose, xylan and wheat straw). A relatively high proportion of the reads was affiliated to Ruminococcaceae suggesting an efficient hydrolytic activity. Knowing that the bacterial community structure is very specific to a particular substrate offers new possibilities to design more efficient H2 -producing biological systems.